PhytoNanotechnology: Enhancing Delivery of Plant Based Anti-cancer Drugs - Khan, Tabassum; Gurav, Pranav (Frontiers in Pharmacology, 2018)
Natural resources continue to be an invaluable source of new, novel chemical entities of therapeutic utility due to the vast structural diversity observed in them. The quest for new and better drugs has witnessed an upsurge in exploring and harnessing nature especially for discovery of antimicrobial, antidiabetic and anticancer agents. Nature has historically provide us with potent anticancer agents which include vinca alkaloids (vincristine, vinblastine, vindesine, vinorelbine), taxanes (paclitaxel, docetaxel), podophyllotoxin and its derivatives (etoposide, teniposide), camptothecin and its derivatives (topotecan, irinotecan), anthracyclines (doxorubicin, daunorubicin, epirubicin, idarubicin) and others. In fact, half of all the anti-cancer drugs approved internationally are either natural products or their derivatives and were developed on the basis of knowledge gained from small molecules or macromolecules that exist in nature. Three new anti-cancer drugs introduced in 2007, viz. trabectedin, epothilone derivative ixabepilone and temsirolimus were obtained from microbial sources. Selective drug targeting is the need of the current therapeutic regimens for increased activity on cancer cells and reduced toxicity to normal cells. Nanotechnology driven modified drugs and drug delivery systems are being developed and introduced in the market for better cancer treatment and management with good results. The use of nanoparticulate drug carriers can resolve many challenges in drug delivery to the cancer cells that includes: improving drug solubility and stability, extending drug half-lives in the blood, reducing adverse effects in non-target organs and concentrating drugs at the disease site. This review discusses the scientific ventures and explorations involving application of nanotechnology to some selected plant derived molecules. It presents a comprehensive review of formulation strategies of phytoconstituents in development of novel delivery systems like liposomes, functionalized nanoparticles, application of polymer conjugates and their advantages over conventional drug delivery systems supported by enhanced biological activity in in vitro and in vivo anticancer assays.